Nutritional Status as an Important Factor in the Health Status of the Adult - J.H.P. Jonxis (Paediatrica Indonesiana, 1975)
Malnutrition in the first year of life may cause permanent damage to the individual. There may be a permanent retardation in growth if the malnutrition is a serious one and the food intake is severely insufficient over a longer, period. Specially when malnutrition occurs in the first months after birth, it may cause damage to the central nervous system.As long as the breast-fed child gets enough breastmilk, it is unlikely that serious problemsÂ  arise. The declinein feeding in many developing countries is a serious problem, especially because the alternatives for human milk are not always available, owing to economic factors. In the, countries of the Western world there exists just, the opposite problem owing to partial over-nutrition abnormalities in fat metabolism may occur, which may influence the health of the individual later on in life.